The Issue of Violence against Transgender People in Prisons - Petrėnaitė, Daiva (Sociologija. Mintis ir veiksmas, 2023)
This article analyses the issue of violence against transgender individuals in prisons, focusing on legislative regulation in various countries. According to the study, transgender people are more likely to commit crimes as a result of systemic discrimination, but they are also more likely to face violent attacks once inside prison. It could be argued that international legal instruments aimed at ensuring transgender rights in prisons are not effective, and they regulate the rights of prisoners in a more general manner. Positive examples of legal regulation regarding the protection of transgender rights in various countries can also be viewed as best practices. This study suggests that legal reforms are required in transgender inmate rights policies to prevent incidents of violence.